PERBANDINGAN TEKNIK RADIOGRAFI CLAVICULA PADA KLINIS FRAKTUR - Ismanto; Vega Melati Putri (JRI (Jurnal Radiografer Indonesia), 2021)
ABSTRACT Background: The clavicle radiograph is one of the examinations that can diagnose fracture pathology. Radiographic examination of the clavicle generally uses the Antero Posterior (AP) and AP Axial projections 15°-30° cranially. But in fact radiology installations differ in using the position of the patient and the direction of the beam. The purpose of this paper is to determine the radiographic technique of the clavicle in clinical fractures from differences in patient position and beam direction and its effect on the results of the picture. Methods: This type of research is descriptive with a literature study approach, looking for research journals on google scholar, and science direct from November to December 2020, using the keywords clavicle, clavicle, clavicle radiograph, clavicle, clavicle fracture, clavicle x-ray. Of the 15 journals obtained, 4 journals met the criteria. Results: Examination using 2 projections is only able to provide visualization from a superior and inferior point of view. Examination using 4 projections is able to show viewing angles from anterior, posterior, inferior, and superior. So it can visualize the image better. The 15cranially AP projection is preferred over the 15caudally AP projection, because the measurement results are not shortened, and the fracture distance is more visible. No statistically significant difference was found for the difference in arm orientation between arm flexion and arm extension in shortening measurements. The degree of change in the location of the fracture image results in a vertical direction significantly shows greater results when the examination is carried out with the patient in an erect position when compared to the supine patient position. Conclusions: Based on the projection, the use of 4 projections can eliminate the effect of clavicle fracture distance, and provide a 3-dimensional image. Giving the direction of the beam with an angle above 15 with a cranially direction produces an optimal picture. In terms of patient position, the optimal image results in the erect position.